Factors Influencing Mothers’ Behavior In Accessing Home Care Services For Mothers And Children At The Moms And Akachan Clinic In 2025 - Nurhafni Nurhafni (Journal of Innovative and Creativity, 2026)
Home care is a healthcare service provided by professionals at the patient's residence, aimed at assisting in meeting the patient’s health needs and addressing health problems. This service is carried out by a professional health team involving family members as supporters in the care and recovery process so that families can become independent in managing health issues. The factors influencing mothers’ behavior in accessing home care services refer to actions or responses individuals make toward a stimulus, which eventually become habitual due to internalized values. Human behavior, in essence, consists of observable and unobservable activities shaped by interaction with the environment and manifested in knowledge, attitudes, and actions. Behavior can be seen as a response to external stimuli—either passive (internal and unobservable) or active (observable). The sample in this study was obtained using the Chi-square test, involving 30 respondents selected from the Moms And Akachan Clinic who met the inclusion criteria. The results of the study showed a significant relationship between mothers’ knowledge and their use of home care services at the Moms And Akachan Clinic in 2025, with a significance value of p = 0.000 < 0.05. It is expected that mothers utilizing home care services can better understand its benefits and be more informed about the different types of accurate home care services available.